Potenzielle kognitive Veränderungen nach Behandlung des benignen Prostatasyndroms: Untersuchungen zu transurethraler Elektroresektion oder 180-Watt-XPSTM-Greenlight-Laserung - Wiedemann, A.; Maykan, R.; Pennekamp, J.; Hirsch, J.; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2015)
Objective: The study was carried out to detect possible changes in cognition after transurethral resection of the prostate (TURP) and 180 W GreenLight-XPS™ laser treatment of the prostate. Methods: Cognitive capacity was assessed by the mini-mental state examination (MMSE) and the clock test preoperatively and on postoperative day 2 in addition to documentation of clinical parameters, such as patient age, prostate size, duration of surgery, comorbidities, co-medications and alterations in hemoglobin (Hb) and sodium concentrations. Results: Patients treated with TURP (n = 88) and 180 W GreenLight-XPS™ laser treatment of the prostate (n = 114) were comparable regarding age, prostate size and duration of surgery. Baseline characteristics of the patients treated by laser showed an increased potential for postoperative cognitive changes with an average of 3.8 comorbidities (TURP 3.11, p = 0.005) and were using an average of 6.79 multiple medications (TURP 5.24, p < 0.001); however, neither the MMSE nor the clock test demonstrated a decrease in the average postoperative score (difference between postoperative and preoperative MMSE + 0.6 ± 1.6 for 180 W GreenLight-XPS™ laser treatment and + 0.6 ± 1.6 for TURP, p = 0.944; difference postoperative and preoperative clock test + 0.43 ± 1.44 for 180 W GreenLight-XPS™ laser treatment and 0.13 ± 1.17 for TURP, p = 0.097). Neither postoperative hemoglobin nor sodium concentrations, as safety relevant parameters, demonstrated clinically relevant changes. The differences between the surgical procedures were not statistically significant. Discussion: Neither 180 W GreenLight-XPS™ laser treatment of the prostate nor TURP demonstrated changes in cognition by comparing the preoperative MMSE and the clock test scores. In this study, the baseline characteristics of laser-treated patients showed a higher number of comorbidities and a higher use of medications, particular those with anticholinergic potency; therefore, 180 W GreenLight-XPS™ laser treatment of the prostate appears particularly safe for elderly patients.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Benign prostatic hyperplasia; Delirium; Laser therapy; Psychometrics; Transurethral resection of prostate